Mechanism of Condensation Enhancement by Corrugated Low Finned Tubes in Presence of Noncondensable Gas. Issue 1 (June 2020) - Ren, Bin; Pu, Zhe; Tang, Xiaoying; Wang, Jifeng; He, Aini; Lu, Hongliang
Abstract: Corrugated tubes are the most convenient reinforcement techniques to enhance intube condensation. In this paper, the average condensation heat transfer coefficients inside the corrugated low finned tube and smooth tube were firstly introduced. The distribution of local heat transfer coefficient was presented at lower and higher inlet noncondensable gas mass fractions. The results show that the major heat transfer resistance is the thermal resistance of liquid film at lower inlet gas fraction. So the mechanism of condensation enhancement by corrugated low finned tubes is the increase of liquid film condensation coefficient. But at higher inlet gas fraction gas layer mass transfer resistance becomes the control thermal resistance. The spiral ribs inside corrugated low finned tube can thinner not only the gas layer thickness but also the liquid film thickness. The mechanism of condensation enhancement is the increase of both gas layer and liquid film condensation coefficient.